PRAKTIK TAX AVOIDANCE PERUSAHAAN OTOMOTIF: PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN - Manja, Manja; Saleh, Muhammad (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
The objective of this research is to examine the influence of profitability, leverage, and company size on tax avoidance practices in manufacturing companies in the automotive and components sub-sector listed on the Indonesia Stock Exchange for the period 2020-2022. The population in this study consists of 38 companies, from which 10 samples with 30 units of analysis were obtained. The data analysis technique used in this research is multiple linear regression analysis. The type of data used in this research is secondary data. The results of the study show that simultaneously, profitability, leverage, and company size have a positive effect on tax avoidance practices. Partial results also show that profitability has a positive impact on tax avoidance practices, leverage has a positive effect on tax avoidance practices, and company size has a positive impact on tax avoidance practices. These findings adopt clear and understandable tax policies, including the amount of tax paid and the tax strategies used, aiming to ensure transparency, feasibility, and legal compliance in managing the company's tax aspects.